Efektivitas Komik Digital Berbahasa Banjar dalam Meningkatkan Literasi Budaya Siswa Sekolah Dasar - Arsyad, M. Ziyan Takhqiqi; Rahman, Abdul (Universitas Muhammadiyah Magelang, 2026)
Digital transformation in education demands the development of innovative learning media that not only improve learning outcomes but also strengthen students' cultural literacy. This study aims to test the effectiveness of Banjar-language digital comics in improving the cultural literacy of elementary school students. The study used a quasi-experimental design with a one-group pretest–posttest involving 75 5th-grade students from three elementary schools in Banjarmasin, namely SDN Belitung Selatan 1, SDN Pelambuan 4, and SDN Sungai Miai 11. The research instrument was a cultural literacy test. Data analysis used descriptive statistics, paired t-tests, and Cohen's d effect size. The results showed a significant increase in students' cultural literacy scores from the pre-test (M = 56.00, SD = 18.80) to the post-test (M = 63.20, SD = 20.20), with a t(74) = 3.20, p < .05 and a medium effect size (d = 0.38). These findings demonstrate that Banjar-language digital comics effectively enhance students' cultural literacy through the integration of visual representations, the Banjar language, and contextual cultural narratives. This research provides an empirical contribution to the development of innovative learning media based on local culture and strengthens the role of learning media in supporting regional language preservation and learning transformation in the digital age.